Autômato celular aplicado no crescimento de câncer - Martins, Caroline Collaço (2010)
In this work we considered cellular automaton model with time delay. The time delay reflects the delay between the time at which the site is affected and the time at which its variable is updated. We analyzed the effect of the rules on the dynamics through the cluster counting. According to this cluster counting, the dynamics behaviour is investigated. We verified the same periodic oscillations as the delay differential equation.